Enantio- and regioselective ene-reductions using F420H2-dependent enzymes. Issue 79 (19th September 2018) - Mathew, Sam; Trajkovic, Milos; Kumar, Hemant; Nguyen, Quoc-Thai; Fraaije, Marco W.
Abstract : A new class of bacterial reductases has been identified that can be used for enantio- and regioselective ene -reductions: F420 -dependent reductases. Abstract : In the past decade it has become clear that many microbes harbor enzymes that employ an unusual flavin cofactor, the F420 deazaflavin cofactor. Herein we show that F420 -dependent reductases (FDRs) can successfully perform enantio-, regio- and chemoselective ene -reductions. For the first time, we have demonstrated that F420 H2 -driven reductases can be used as biocatalysts for the reduction of α, β-unsaturated ketones and aldehydes with good conversions (>99%) and excellent regioselectivities and enantiomeric excesses (>99% ee). Noteworthily, FDRs typically display an opposite enantioselectivity when compared to the well established FMN-dependent Old Yellow Enzymes (OYEs).